ORGANOLEPTIC CHARACTERISTIC AND WATER HOLDING CAPACITY OF BALI DUCKS MEAT (Anas sp) RESULT OF Immersing Extract Rosella flower (Hibiscus sabdariffa Linn) - D. P. P., Angin; Umiarti, A. T.; Okarini, I. A. (Jurnal Peternakan Tropika; Vol 10 No 3 (2022): Vol. 10 No. 3 Tahun 2022; September - December, 2022)
Duck meat is a type of poultry that is starting to get a lot of demand but still has drawbacks, namely tough meat, dark red meat color and a fishy smell, so it is necessary to soak or marinate with rosella flower extract. This study aimed to determine the organoleptic quality and water-holding capacity of eight-week-old bali duck (Anas sp) from the extract of rosella flower (Hibiscus sabdariffa Linn), which was carried out at the Laboratory of Animal Products Technology and Microbiology, Faculty of Animal Husbandry, Udayana University, Bali. This study used a completely randomized design (CRD) with four treatments and five replications to obtain 20 experimental units. The four treatments: without immersion (P0), immersion in 5% extract (P1), immersion in 10% extract (P2), immersion in 15% extract (P3), with immersion time of P1, P2 and P3 for 60 minutes. The variables observed were organoleptic tests of aroma, taste and texture which were assessed by 15 semi-trained panelists as well as the physical quality of water holding capacity (DIA). The results of this study showed that soaking rosella flower extract to a level of 15% for 60 minutes showed significantly different results (P<0.05) on aroma, texture, water holding capacity, but not significantly different (P>0.05) on taste. The conclusion of this study is that the immersion with rosella flower extract up to a level of 15% on the organoleptic value of cooked meat tends to increase, the aroma is 2.47-7.53 (no smell of rosella-very smells of rosella), the taste is 4.87-6.00 (neutral-mildly delicious) and textures 4.73-6.73 (neutral-soft). The average water holding capacity (DIA) of duck meat also tends to increase from 62.77 to 68.31%. Keywords: rosella flower, bali duck meat, immersion, water holding capacity and organoleptic test